Letter: vedolizumab for autoimmune liver disease associated inflammatory bowel disease. Issue 10 (19th April 2018) - Pavlidis, P.; Graham, J.; Gulati, S.; Dubois, P.; Heneghan, M.; Joshi, D.; Hayee, B.
Abstract : Linked Content This article is linked to Christensen et al papers. To view these articles visit https://doi.org/10.1111/apt.14525 and https://doi.org/10.1111/apt.14638 .